2022
DOI: 10.1213/ane.0000000000005905
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Fever Associated With Continuous Spinal Versus Epidural Labor Analgesia: A Single-Center Retrospective Study

Abstract: BACKGROUND: Neuraxial labor analgesia is associated with elevations in maternal temperature; the mechanism responsible is unknown. Proposed mechanisms have included infection, altered thermoregulation, and inflammation, potentially triggered by local anesthetics. Studies of the association between neuraxial labor analgesia and maternal fever have focused on epidural analgesia, and there have been no comparisons of the rate of maternal fever between continuous spinal and epidural labor analgesia. METHODS: We pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Similarly, we also found the incidence of fever increased in the ELA group compared with that of patients who did not receive ELA in the present study. Although the mechanisms by which intrapartum fever develops as a result of ELA remain unclear, numerous studies suggest that maternal fever during delivery may be a consequence of non-infectious inflammatory resulting from central neuraxial blockade 26–28. Fever during labour with ELA may be associated with adverse maternal outcomes and increased risk of neonatal complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, we also found the incidence of fever increased in the ELA group compared with that of patients who did not receive ELA in the present study. Although the mechanisms by which intrapartum fever develops as a result of ELA remain unclear, numerous studies suggest that maternal fever during delivery may be a consequence of non-infectious inflammatory resulting from central neuraxial blockade 26–28. Fever during labour with ELA may be associated with adverse maternal outcomes and increased risk of neonatal complications.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms by which intrapartum fever develops as a result of ELA remain unclear, numerous studies suggest that maternal fever during delivery may be a consequence of non-infectious inflammatory resulting from central neuraxial blockade. [26][27][28] Fever during labour with ELA may be associated with adverse maternal outcomes and increased risk of neonatal complications. Recent studies have shown that among those receiving ELA, women who developed intrapartum fever had a significantly longer first stage of labour and a higher incidence of caesarean deliveries, assisted vaginal delivery, intrapartum haemorrhage and turbid amniotic fluid than those with no intrapartum temperature elevation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, duration of exposure to epidural analgesia or length of labor in unmedicated women remains a risk factor for intrapartum fever 1 . There is no evidence that the rates of fever or exposure to inflammatory cytokines are altered with traditional epidural when compared with combined spinal epidural or continuous spinal analgesia nor with patient-administered epidural boluses 3 . No specific neuraxial technique has been recommended to reduce maternal fever or fetal inflammation 1…”
Section: Commentmentioning
confidence: 99%
“…1 There is no evidence that the rates of fever or exposure to inflammatory cytokines are altered with traditional epidural when compared with combined spinal epidural or continuous spinal analgesia nor with patient-administered epidural boluses. 3 No specific neuraxial technique has been recommended to reduce maternal fever or fetal inflammation. 1 Several studies have evaluated the effects of local anesthetic medications on inflammatory pathways.…”
Section: Commentmentioning
confidence: 99%
“…The article by Seiler et al 1 in this issue of Anesthesia & Analgesia examines the difference in the rate of maternal fever in patients with continuous spinal analgesia as compared to those with epidural labor analgesia. Multiple investigations have concluded that the fever associated with neuraxial analgesia is not related to maternal or fetal infection.…”
mentioning
confidence: 99%